Offload Debugging for Java Programmed Embedded Systems - Fragoso, Fernando Henrique Silva; Tenório, Luiz Fernandes Eugênio; Meira, Sílvio Romero de Lemos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Small devices are running software ever more complex. In this scenario, which has been expanding with trends such Internet of Things (IoT) and Ubiquitous computing, becomes even more significant the process of debugging. The use of high-level language virtual machines (VM) on embedded systems can avoid issues on the portability, safety and memory management. However, it presents challenges for debugging due to lack of memory resources and VM's hardware abstractions. This paper presents an out-of-process Java Virtual Machine (JVM) debugger based on the Java Platform Debugger Architecture (JPDA). The proposed method reduces the complexity of debug implementation inside the VM itself without loosing the link between Java and native code. Thus, it allows the debugging using the high-level language instead of native compiled code.